Dynamic behavior of an axially moving wide web. - Cedrowska, Agnieszka; Marynowski, Krzysztof (Polskie Towarzystwo Mechaniki Teoretycznej i Stosowanej, 2012)
Theoretical and experimental dynamic analysis of an axially moving wide composite web is presented in this paper. The mathematical model of the system under consideration has the form of a differential equation with partial derivatives. The approximate solution using the extended Galerkin method has been determined in this work. Dynamic analysis allowed one to determine the natural frequency of bending and torsional vibrations of the web. Experimental investigations of dynamic behavior of the axially moving web was performed on a laboratory stand in the form of belt transmission. The experimental verification of numerical studies concerned the lowest frequencies of bending and torsional vibrations. The fundamental frequency of bending vibration was determined numerically with the greatest accuracy. accuracy.

W pracy przedstawiono teoretyczno-doświadczalną analizę dynamiczną przesuwającej się osiowo szerokiej kompozytowej wstęgi. Model matematyczny rozpatrywanego układu ma postać równania różniczkowego o pochodnych cząstkowych. Przybliżone rozwiązanie modelu matematycznego zostało określone przy wykorzystaniu rozszerzonej metody Galerkina. Analiza dynamiczna umożliwia wyznaczenie częstotliwości drgań własnych giętych i skrętnych wstęgi. Badania eksperymentalne dynamiki przesuwającej się osiowo wstęgi zostały przeprowadzone na stanowisku laboratoryjnym w postaci przekładni pasowej. Eksperymentalna weryfikacja badań numerycznych dotyczyła wyznaczenia najniższych częstotliwości drgań giętnych i skrętnych wstęgi. Podstawowa częstotliwość drgań giętnych została wyznaczona w badaniach numerycznych z największą dokładnością.
Dynamika szerokiej wstęgi przesuwającej się osiowo.
Keywords: axially moving plate; dynamic analysis; experimental verification; analiza dynamiczna; kompozytowa wstęga; model matematyczny; równanie różniczkowe; metoda Galerkina; częstotliwość drgań; przesuwająca się osiowa wstęga